Rekayasa Prompt untuk Pustakawan menggunakan ChatGPT 4o - Utomo, Nadzir Cahyo; Destrianto, Mochammad Riski (Perpustakaan Nasional, 2024)
The era of artificial intelligence usage has become increasingly massive lately. One of them is the use of ChatGPT-4o. ChatGPT is a generative artificial intelligence developed by OpenAI. ChatGPT-4o is the latest large language model released by OpenAI for ChatGPT. It is important for librarians not only to understand the current developments in artificial intelligence but also to master the skills relevant to artificial intelligence. Prompt engineering is a field of study that is relevant to artificial intelligence and the profession of librarianship. This research aims to identify prompt construction techniques in prompt engineering that are relevant for librarians to enhance their competencies in the field of artificial intelligence. This research is a qualitative study, as the author uses qualitative descriptive data in this research. The method of data collection used by the author in this research is literature study. The findings of this research are five prompt engineering techniques that librarians can use in carrying out their professional duties and responsibilities. Based on the implementation and testing conducted by the author, formalizing prompts is the most comprehensive prompt formulation technique in this research. This research shows that librarians can learn and master prompt engineering skills at a basic level. The recommendation from this study is that librarians need to actively engage in learning and mastering prompt engineering with the aim of enhancing their competencies. Furthermore, librarians who have mastered prompt engineering can play an important role in educating patrons about prompt engineering.